Identification of critical thinking: suku (supik and kulub) on electricity material in Jambi Province. Issue 1 (March 2021) - Hendriyani, D; Siahaan, P; Samsudin, A
Abstract: The world of education is in line with advances of science and technology, the facilities obtained by students and the ability to teach teachers in training students to think critically are factors that influence differences in the level of critical thinking students. The purpose of this study was to determine the differences between supik and kulub critical thinking skills. The type of this research was a survey study that illustrated how differences in students' critical thinking skills in a region of Jambi province. The participants consisted of 6 female students, commonly called "SUPIK" and 4 male students, who were usually called "KULUB". The average student involved comes from the Malay ethnic group, the native Malay ethnic group from Jambi Province. The research instrument used was a test of critical thinking skills. The results of this survey research showed the differences in the ability of supik and kulub critical thinking skills in one region of Jambi Province in learning electricity. This study has limitations because the number of samples used is so small. So, the need for further research by involving more sample and to see in more detail the causes of differences in the critical thinking abilities of supik and kulub .